THE ROLE OF SOCİAL NETWORKİNG SİTES TOWARDS SPREADİNG HATE SPEECH AMONG HEBRON UNİVERSİTY STUDENTS "FACEBOOK EXAMPLE" (American Journal of Research in Humanities and Social Sciences, 2023)
Social networks play an important role in introducing hate speech among social network users through its platforms, and this is confirmed by the increasing demand by different segments of society for these networks, and from here this study came to identify the role of social networking sites towards spreading hate speech among Hebron University students. This study is considered one of the descriptive studies in which the researcher resorted to the survey method, in which he studied the audience of Facebook users through a sample of Hebron University students who numbered (125) using a survey sheet consisting of (20 questions) represented through four axes, based on my theories Dependence on the media, uses and gratifications. The study showed the most prominent results, which showed the significant and clear impact of Face book in spreading hate speech among Hebron University students, at a rate of (53%) and (50%) for each of the societal, verbal and behavioral violence and the spread of hate speech, respectively. It also showed the impact of hate speech spread through the Facebook platform. Book on the system of religious and social values in the Palestinian society because it focuses on tribal, clan and political fanaticism away from the arbitration of reason, logic and religion in resolving disputes and disagreements, with a percentage of (63%). Based on these results, the researcher recommended the need for the Ministry of Higher Education and Scientific Research to pay attention to the issue of hate speech, by allocating lectures and offering community courses related to the topic, and the urgent need for civil society and clan institutions to stand up to their responsibilities and contribute to spreading a culture of tolerance and rejecting and combating hate.